Classification and diagnosis of colorectal dysplasia in inflammatory bowel disease. Issue 7 (July 2015) - Lam-Himlin, Dora; Bhaijee, Feriyl; Arnold, Christina
Abstract In patients with ulcerative colitis or Crohn colitis, the risk for dysplasia and colorectal cancer increases with disease duration, and early detection by surveillance colonoscopy has been the mainstay for preventive treatment. For these diseases in which the clinical management relies heavily upon pathologic interpretation, the diagnosis and grading of dysplasia remains inherently challenged by interobserver variability. This diagnostic challenge is coupled with new developments in endoscopic techniques resulting in relatively rapid shifts in terminology and changes in the macroscopic classification of dysplastic lesions. This article provides pathologists with an update on the preferred macroscopic classification, details the histologic features of dysplasia and utility of immunohistochemistry, and provides a historical context for outdated terminology.